Pengaruh Kebijakan Dampak Keilmuan Akuntansi Manajemen di Lingkungan Perusahaan Swasta di Kota Surakarta Berbagai Macam Sektor Usaha - Rima Parawati Bala; Totok Susilo Pamuji Nugroho; Edi Priyono (STIE Atma Bhakti, 2026)
The increasingly dynamic business environment requires private companies to have information management systems that support fast, precise, and accurate decision-making. One of the key aspects contributing to organizational success is the application of management accounting principles and knowledge. This study aims to analyze the influence of policies regarding the implementation of management accounting knowledge on the sustainability of private companies in Surakarta City. The study employed a qualitative approach using a field study method. The research informants consisted of company leaders, finance managers, operations managers, and accounting staff from 45 private companies in Surakarta City, selected using purposive sampling. Data were collected through in-depth interviews, observations, and documentation, while data analysis employed the interactive model developed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results indicate that corporate policies concerning the implementation of management accounting principles have a highly significant impact on decision-making effectiveness, operational efficiency, cost control, budgeting, performance evaluation, and the enhancement of corporate competitiveness. Most companies stated that management accounting information serves as a primary basis for determining business strategies, managing risks, and maintaining business sustainability amid changes in the business environment. This study confirms that management accounting knowledge has evolved beyond merely serving as a tool for cost recording and has become a strategic instrument that supports sustainable corporate success